Outcome of staged injection of autologous platelet rich plasma in treatment of mild to moderate knee osteoarthritis - Gupta, Rajat; Avtar, Ram; Kumar, Krishan (International Journal of Research in Orthopaedics, 2019)
Background: Autologous platelet-rich plasma (PRP) offers an easy solution for delivering multiple growth factors needed for tissue repair. Intra-articular injections of PRP have been proposed as a simple low cost minimally invasive way to obtain the concentration of growth factors and biologically active molecules to promote cartilage healing in osteoarthritic (OA) knee joint. The objective of the present study was designed to evaluate the clinical efficacy of autologous platelet rich plasma injection in mild to moderate osteoarthritic knee and to assess the role of serial staged autologous platelet rich plasma injection. Methods: 50 patients with mild to moderate osteoarthritis of knee were divided into two groups. Group A was given staged injection of freshly prepared autologous PRP in the affected knee. Group B was given single injection of PRP. The Results were evaluated on the basis of the Western Ontario and McMaster Universities Arthritis Index (WOMAC) questionnaire and visual analog scale (VAS) before treatment and 3 weeks, 8 weeks, 16 weeks and 24 weeks after treatment. Results: At 24-weeks follow up the following observations were made; the MeanVAS in Group A decreased to 3.30 whereas in Group B it increased to 4.54. The Mean WOMAC score in Group A was reduced to a mere28.64 in Group A and in Group B it was 39.76. Conclusions: It is concluded from our study that concomitant use of serial staged injection (two) of PRP over four months is more effective than single injection in patients with mild to moderate OA of knee.